Aspek Sosial Budaya yang Mempengaruhi Upaya Promosi Kesehatan Obesitas pada Anak: A Systematic Review and Meta-Synthesis Of Qualitative Studies - Edy Gunawan; Dian Ayubi (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: The high incidence of obesity also occurs in children with a prevalence that continues to increase from year to year. Local socio-cultural aspects are often the cause of obesity in children. Sometimes the promotive and preventive efforts that are carried out experience obstacles from the socio-cultural aspect. Objectives: This study aims to synthesize research findings regarding socio-cultural aspects of health promotion efforts in the incidence of childhood obesity. Research Metodes: The study in this study was conducted using systematic review methods and meta-synthesis studies. The data search was carried out using 3 (three) databases, namely PubMed, Science Direct, Taylor & Francis with certain keywords and the 2017-2021 research study range. Results: There are several socio-cultural aspects related to the incidence of obesity in children, namely peers, home environment, school environment, access, and economy. Conclusion: Socio-cultural aspects have both positive and negative influences on promotive and preventive efforts in cases of childhood obesity, therefore the socio-cultural aspects must be a serious concern in solving local specific problems.